2006
DOI: 10.1063/1.2399352
|View full text |Cite
|
Sign up to set email alerts
|

Facile strategy and mechanism for orthorhombic SnO2 thin films

Abstract: Orthorhombic phase SnO2 is a material with unknown optical, electrical, and gas-sensing properties. It was found previously only at high pressures and temperatures. A facile strategy for the synthesis of orthorhombic SnO2 is of fundamental importance. Using pulsed-laser deposition, the authors report a kind of experimental realization of a pure orthorhombic SnO2 thin film under low pressure and temperature that are much lower than those of traditional methods. The optical properties of an orthorhombic SnO2 thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 20 publications
2
54
0
3
Order By: Relevance
“…1 of our paper 4 shows the presence of a significant amount of the amorphous phase. Typical x-ray diffraction spectra of the amorphous phase show a broad convex shape, 5,6 which are very different from that reported in Fig.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…1 of our paper 4 shows the presence of a significant amount of the amorphous phase. Typical x-ray diffraction spectra of the amorphous phase show a broad convex shape, 5,6 which are very different from that reported in Fig.…”
mentioning
confidence: 49%
“…9 ͑iv͒ Reid 3 pointed out that we made the following statement in one of our earlier paper: 10 "In general, for pulsed laser deposition of SnO 2 thin films grown under room temperature, the amorphous phase is ineluctable." However, for the paper in question, 4 the orthorhombic phase SnO 2 thin films were prepared under a substrate temperature of 320°C and not at room temperature.…”
mentioning
confidence: 99%
“…In these studies, SnO 2 in orthorhombic structures was found to exhibit better sensitivity for specific gases than the tetragonal rutiletype structure (Arbiol et al, 2008;Sangaletti et al, 1997). However, natural SnO 2 , known as cassiterite, always exists as the rutile-type structure and it is generally difficult to obtain the orthorhombic phase directly from minerals (Chen et al, 2006). Therefore, finding new methods for producing SnO 2 with orthorhombic structures, such as by pressure tuning (Haines & Leger, 1997), is of particular interest in the sensor industry.…”
Section: Sno 2 Nanobelts and Nanowires Under High Pressuresmentioning
confidence: 99%
“…2 Although the generation of a pure film containing this metastable phase is an important goal, a careful examination of their data in light of other work fails to support this claim.…”
mentioning
confidence: 99%